Educational value of Sport: Promoting motor activity - Mattia Caterina Maietta; Lucia Martiniello (Pensa MultiMedia, 2024)
The following work is aimed at the study of the practice of sport as an instrument of social wellbeing, prevention of illnesses and a source of sociability. It aims to offer an interpretative framework of the Italian Constitution and to propose an examination of good practices already existing at national and international level. Examples of good practice include the Dual Career of student athletes. The continuous expansion of the sports movement in general has meant that it has become part of many and varied sectors of society, and consequently, society has also had to adapt to this new reality. It is for this reason that sport has established itself as a component of fundamental importance and no longer placed on the margins of multiple contexts of social interaction.